2022
DOI: 10.1039/d1gc03396d
|View full text |Cite
|
Sign up to set email alerts
|

Eco-friendly processes for the synthesis of amorphous calcium carbonate nanoparticles in ethanol and their stabilisation in aqueous media

Abstract: New understandings in the amorphous calcium carbonate nanoparticle synthesis lead to a final mass concentration increase by a factor of 3.5. The stabilisation in aqueous media is achieved by a 2-minute scalable process using bio-sourced stabilisers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 94 publications
(310 reference statements)
0
9
0
Order By: Relevance
“…More recent studies have followed the crystallization of protodolomite [34], as well as the role of Mg with water in triggering crystallization [35]. Focusing on the role of solvent polarity, there is also extensive work to understand mechanisms that control phase selectivity during precipitation from water-EtOH mixtures, many of which involve amorphous precursor stages [36][37][38]. Interestingly, some results indicate that Ca 2+ and CO 2− 3 ions have different solvation tendencies in water-EtOH mixtures, resulting in local inhomogeneity [39], which can in some cases cause a disordered ACC that does not have proto-crystalline local structures [40].…”
Section: Fir and Amorphous Carbonatesmentioning
confidence: 99%
“…More recent studies have followed the crystallization of protodolomite [34], as well as the role of Mg with water in triggering crystallization [35]. Focusing on the role of solvent polarity, there is also extensive work to understand mechanisms that control phase selectivity during precipitation from water-EtOH mixtures, many of which involve amorphous precursor stages [36][37][38]. Interestingly, some results indicate that Ca 2+ and CO 2− 3 ions have different solvation tendencies in water-EtOH mixtures, resulting in local inhomogeneity [39], which can in some cases cause a disordered ACC that does not have proto-crystalline local structures [40].…”
Section: Fir and Amorphous Carbonatesmentioning
confidence: 99%
“…With increasing water content (from 100 μL to 300 μL), the particle size of the formed nanoparticles also increased from 139.9 ± 1.6 nm to 176.6 ± 0.7 nm. Because CCN are insoluble in anhydrous ethanol, the reaction was performed in anhydrous ethanol containing trace amounts of water, which effectively prevents spontaneous aggregation and deposition of nanoparticles [24]. The solubility of NH 3 and CO 2 in water is much higher than that in ethanol.…”
Section: Effect Of Water Contentmentioning
confidence: 99%
“…In contact with water, they self-dissolve and crystallize into other polycrystalline forms of calcium carbonate. In contrast, after phospholipid modification, phospholipids provide a waterproof coating for the protection of CCN particle size and morphology, thus potentially addressing the problem of instability of amorphous CCN in water [24,26]. The average particle sizes of CCN dispersed in absolute ethanol and water were 138.6 ± 1.10 nm and 4523.7 ± 103.0 nm, respectively (Figure S1).…”
Section: In Vitro Characterization Of Uno@ccnmentioning
confidence: 99%
“…8 Based on this, in our previous studies, 9,10 we reported a dyeing method for cotton fibres using high contents of EtOH instead of water (H 2 O), demonstrating that the EtOH-H 2 O mixture is a good dyeing medium with the industrial scale-up. Besides, the EtOH-H 2 O mixture is also widely used in numerous chemical industries such as food processing, 11 medical protection, 12 cosmetics, 13 pharmaceuticals, 14,15 fuel, 16 and textiles. 17 Therefore, more important consideration should be given to the development of a sustainable recovery system that supports greener and cleaner production, together with the life cycle assessment.…”
Section: Introductionmentioning
confidence: 99%